Comparing the aromatic profile of seven unheated edible insect species. (February 2023) - Perez-Santaescolastica, Cristina; De Winne, Ann; Devaere, Jolien; Fraeye, Ilse
Graphical abstract: Highlights: High importance of flavour in product acceptability. Different aroma profiles among unheated insect species. High content of acetic acid in most insects. More unpleasant aroma compounds in Zophobas morio . Abstract: Insects and insect-based products have gained increasing interest as human food because of their many technological, nutritional and environmental advantages, but they are still rejected by many Western consumers. Analytical knowledge of flavour compounds could contribute to enhancing product attractiveness to consumers. Therefore, the goal of this study was to examine the volatile compound profiles of 7 unheated insects: Zophobas morio (ZM), Tenebrio molitor (TM), Locusta migratoria (LM), Galleria mellonella (GM), Blaptica dubia (BD), Alphitobius diaperinus (ALD) and Acheta domesticus (ACD). A total of 67 compounds were identified. Carboxylic acids were predominant in ALD, BD, GM, TM and ZM, while ketones were the major family in ACD and linear hydrocarbons in LM. ZM contained the highest number of unpleasant odour compounds, including indole, also present in BD and GM, which is characterised by a low detection threshold.